2018
DOI: 10.5194/acp-18-1507-2018
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the physical multiphase interactions of HNO<sub>3</sub> between snow and air on the Antarctic Plateau (Dome C) and coast (Halley)

Abstract: Abstract. Emissions of nitrogen oxide (NO x = NO + NO 2 ) from the photolysis of nitrate (NO − 3 ) in snow affect the oxidising capacity of the lower troposphere especially in remote regions of high latitudes with little pollution. Current air-snow exchange models are limited by poor understanding of processes and often require unphysical tuning parameters. Here, two multiphase models were developed from physically based parameterisations to describe the interaction of nitrate between the surface layer of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Recent modelling suggests that co-condensation is the most important process explaining NO3incorporation in snow undergoing temperature gradient metamorphism at Dome C (Bock et al, 2016). Diamond dust can also scavenge high concentrations of HNO3 at Dome C (Chan et al, 2018). Furthermore, the top layer of the snow pack is only 1 mm thick in the TRANSITS model, which is where we would expect the highest concentrations due to the exponential decay of NO3with depth (Fig.…”
Section: Validation Of Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Recent modelling suggests that co-condensation is the most important process explaining NO3incorporation in snow undergoing temperature gradient metamorphism at Dome C (Bock et al, 2016). Diamond dust can also scavenge high concentrations of HNO3 at Dome C (Chan et al, 2018). Furthermore, the top layer of the snow pack is only 1 mm thick in the TRANSITS model, which is where we would expect the highest concentrations due to the exponential decay of NO3with depth (Fig.…”
Section: Validation Of Resultsmentioning
confidence: 83%
“…In addition, the uptake is not dependent on the HNO3 concentration in the air (Abbatt, 1997). However, the seasonal temperature difference at an individual site (i.e., DML or Dome C) is far greater, which could allow a seasonal dependence on the uptake and loss of NO3in the skin layer, which results in the retention of a greater proportion of NO3in summer (Chan et al, 2018).…”
Section: Dry Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the model does not reproduce the summer observations at the coast, where the temperature, relative humidity and concentration of aerosol in air and snow are much higher than that on the Plateau, and where snow surface melt is possible, strengthening previous theory of several photolytic domains aforementioned. Nonetheless, Chan et al (2018) developed a new model and concluded that winter air-snow interactions of nitrate between the air and skin layer snow can be described as a combination of non-equilibrium surface adsorption and co-condensation on ice, coupled with solid-state diffusion inside the grain, similar to Bock et al (2016). In addition, Chan et al (2018) were able for the first time to reproduce the summer observations on the Antarctic Plateau and at the Coast, concluding that it is the equilibrium solvation into liquid micro-pockets, based on Henry's solubility law, that dominates the exchange of nitrate between air and snow at warmer sites, that is, where the temperatures are above the eutectic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…photolysis in snow (Chan et al, 2018). Therefore, a robust quantification of the NO x E sources on a continental scale over Antarctica is still lacking (Frey et al, 2013(Frey et al, , 2015Legrand et al, 2014;Savarino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%